Pengaruh Perubahan Pendapatan dan Biaya Telekomunikasi Terhadap Konsumsi Rumah Tangga Indonesia - Indrawati, Riannie (Politeknik Statistika STIS, 2024)
This study aims to determine the effect of changes in income and telecommunication expenditure on Indonesian household consumption using Susenas data for 2019. The household expenditure structure was analyzed using the AIDS model and SUR estimation. The estimation results show the income elasticity of telecommunication in 2019 is 1,2923 which indicates that telecommunications are luxury goods that are elastic to changes in income. The own-price elasticity for telecommunication is -0,5510 so that telecommunications are price inelastic.